2021
DOI: 10.5755/j01.ee.32.3.28621
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption Patterns in Different Settings

Abstract: The purpose of this study is to identify sustainable consumption patterns of Lithuanian consumers based on their sustainable consumption behaviour in two settings: at home and at work. The study also attempts to describe the segments and highlight their differences in terms of consumer engagement into sustainable consumption, which in the present study reflects the psychological state of consumers, determining their actual behaviour. The study sample consisted of 498 Lithuanian consumers. A two-step cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 50 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…According to Piligrimienė, et al (2019), the workplace influences one's consumer behavior because of the experiences acquired by employees while at work, which becomes a factor for stimulating sustainable consumption at home. They found that work-life balance and sustainable consumption at home are positively related.…”
Section: And Its Impact On Work Effectivenessmentioning
confidence: 99%
“…According to Piligrimienė, et al (2019), the workplace influences one's consumer behavior because of the experiences acquired by employees while at work, which becomes a factor for stimulating sustainable consumption at home. They found that work-life balance and sustainable consumption at home are positively related.…”
Section: And Its Impact On Work Effectivenessmentioning
confidence: 99%
“…Since COVID-19, the scholarly interest in studying the impact of work-life balance on wellbeing has increased severalfold, due to concerns related to teleworking and increased job stress (Irawanto et al, 2021). Greater emphasis on work-life balance could lead to increased emphasis on sustainable consumption, such as resource efficiency, eco-conscious buying, and healthy lifestyles, amongst others (Piligrimienė et al, 2019). There is also the growing debate regarding a shorter work week, and great focus on the quality of work rather than the quantity or number of hours worked (Wang et al, 2022 ).…”
Section: Micro-level Factorsmentioning
confidence: 99%
“…Green finance in the form of green credit provided by the financial institutions to the organizations and also in the form of renewable energy production would lead the country towards economic growth (Cheba et al, 2020;Haroon et al, 2021;Piligrimienė et al, 2021). In addition, green finance has played a significant role in the recovery of the economy after Covid-19 lockdown and improved the countries' economic condition.…”
Section: Literature Reviewmentioning
confidence: 99%